Urban Ex-Landfill as Built Environment: Community Perception - Mazifah Simis (Journal of Architecture, Planning and Construction Management, 2020)
The continuous process of urbanism and urban sprawl has resulted 115 numbers of ex-landfill site become a part of the city’s image and the urban built environment. The urges to meets the needs of urban society for improve quality of life and adequate urban spaces in tandem with the increase of urban economic and social development become the demanding factor to redevelop ex-landfill site within the urban vicinity. In the context of development in Malaysia, five types of redevelopment of ex-landfill site have been identified; including the redevelopment as a public park. Redevelopment of ex-landfill site as public park is often regards as the most ideal development. The redevelopment is said be able to mitigate the environmental problems that exist due to the effects of ex-landfill contamination and create improvement in the quality of life, recreational and social well-being of urban society. However, questions on what is the main issues of ex-landfill site in accordance with the perception of local community, what type of priority scale on the redevelopment of ex-landfill according to the Malaysian public opinion and is the redevelopment of public park at the ex-landfill site is acceptable to the Malaysian society, arise as problem question. Thus, this paper attempts to answer the questions based on the community perception. By using the respondent perception’s data which is community surrounding the ex-landfill site and public park at the ex-landfill site; and also expert’s perception, the results indicate the suitability of the redevelopment of the ex-landfill site in the future Malaysia urban development.